Bibliometric analysis of studies on the treatment of hemifacial spasm - Fang, Li-Jun; Wang, Chen-Yao (Frontiers in Neurology, 2022)
Objective: Hemifacial Spasm (HFS) is a common neurological disorder of the brain, which is difficult to treat. Most patients are distracted by it and are unable to work or study normally, which seriously affects their physical and mental health. However, there are few bibliometric studies on it. This paper researched the articles on HFS using a bibliometric approach. Method: Articles about HFS were retrieved from the Web of Science (WoS) Core Collection database. We employed the Visualization of Similarities (VOS) viewer to analyze these publications. Results: A total of 645 reviews or articles in English were retrieved from WoS, in this study, we found that the number of publications showed a rising trend and China is the most active in researching the treatment of HFS. About keywords, neurosciences & neurology was the researched (422 times), followed by hemifacial spasm (420 times), surgery (320 times). By assessing the organizations, Shanghai Jiaotong University published the most papers (8.68%), followed by Sungkyunkwan University (3.26%), and Baylor College Medicine (2.64%). A total of 247 journals have delivered publications on the treatment of HFS, World Neurosurgery (44 papers) published the largest number of articles. Conclusion: The annual publications increased with a fluctuating tendency. More researchers are taking an interest in HFS. This study helps us find out the hotspot and trend in research about facial spasm treatment.